Implementing community-based interventions for the management of chronic conditions in low- and middle-income countries: A scoping review of qualitative evidence. - Syreen Hassan; Nancy Kagwanja; Brahima Diallo; Robinson Oyando; Pablo Perel; Anthony Etyang; Benjamin Tsofa; Ellen Nolte; IHCoR-Africa Collaborators (PLOS Global Public Health, 2025)
The rising prevalence of chronic diseases in low- and middle-income countries (LMICs) poses significant challenges to already overburdened health systems. Community-based interventions are recognised as effective strategies for managing these conditions. However, implementing such interventions faces barriers that can hinder their effectiveness. This scoping review aims to assess qualitative studies examining barriers and facilitators to implementing community-based interventions for chronic disease management in LMICs. We searched six databases for studies published between 2013-2024. Eligible studies were those with a qualitative design that explored implementation challenges and facilitators of community-based interventions. Data were thematically analysed and interpreted using the Socio-Ecological Model (SEM) to capture multi-level influences on implementation. Eighteen studies were included, covering interventions in 13 LMICs. We identified four levels of influencing the implementation of chronic condition management interventions: individual (service users and providers), community, health system/policy, and interpersonal. Barriers at the individual level included privacy concerns, misconceptions about CHW roles, and a preference for traditional medicine. Facilitators included strong CHW motivation, often driven by personal experiences with the conditions they managed. Community-level support, particularly from local leaders and sensitization events, enhanced intervention acceptance. At the health system level, training quality and role recognition of CHWs were critical, while barriers included excessive workload and insufficient infrastructure. Interpersonal relationships, especially gender dynamics and attitudes of facility-based workers towards CHWs, also influenced implementation outcomes. The quality of qualitative evidence varied, with many studies lacking clear objectives and data collection or analysis frameworks. Effective implementation of community-based interventions for chronic disease management in LMICs requires addressing both systemic and interpersonal barriers. Future interventions should emphasise structured community engagement, comprehensive training, and better integration with healthcare systems. Additionally, improving the methodological rigor of qualitative research is essential for gaining deeper insights into the complex factors that influence the success and sustainability of these interventions.